PEMIKIRAN TAUHID TGH. UMAR KELAYU DALAM KITAB MANZARULAMRAD FI BAYANI QITH'ATIN MINALl'TIQAD - Adi Fadli (UIN Sunan Kalijaga Yogyakarta, 2015)
This writing will specifically explore the thought ofTGH Umar Kelayu a teacher of teachers in Lombok and surrounding area. TGH Umar Kelayu is well known in various Islamic studies, such as Quran, hadits, tauhid, tasawuf, nahwu, sharaf, balaghah. By focusing in text called Manzarul Amrad ff Bayani Qith 'atin Mina! I tiqddi can be concluded that the tauhid's thought ofTGH Umar Kelayu is including to Ahlussunnah wal Jama' ah, i.e. based on the Asy' ariyah and Maturidiyah. According to the content of basic tauhid's material of the text, the target audiences ofTGH Umar Kelayu are the common Muslim, since the basic tauhid is important to the Muslims. The text Manzalu Al-Amradi fi Bayani Qith 'atin min al- 'Iqtiqddi explicates tauhid briefly in three divisions. First part explains wajib, mustahil, and jaiz character ofAllah; second part explains wajib, mustahil, and jaiz character of the prophet; and third part explains the rukun iman. All this parts are explained briefly, shortly, and clearly with their dalil naqli and aqli with the real examples.